ANALISIS PENDAPATAN DAN PEMASARAN USAHA PEMBUATAN GARAM DI KELURAHAN TALISE KECAMATAN MANTIKULORE KOTA PALU - Ismail, Hermina (AGROTEKBIS, 2015)
This research aims to understand how much income received by farmers salt, to know marketing channel, the margin, and the efficiency of marketing. Study was conducted in October until December 2014, located in Kelurahan Talise Mantikulore sub-district Palu. The determination of respondents were with a method of random simple (Simple Random Sampling) with the total sample 34 farmers from 160 to commodity farmers salt. Traders done by means of the sample collection method tracing sampling so acquired as many as 6 middle-man. Analysis method used is an analysis of income and marketing analysis. The results of research suggests that the average income salt in Kelurahan Talise Mantikulore a Palu in one city in the production of Rp 17.294.563 times. The analysis showed that the marketing of marketing channels salt in kelurahan talise only one channel marketing, namely the farmers and traders to the consumer end. The analysis of marketing margins salt on a tract omnipresence namely mt Rp 25,000, and efficiency of marketing show that marketing talise urban village in the level of farmers to middle-men worth 100 % and in the middle-men to the consumer of 58,33% and 61,53 %.